Health policy implementation challenges in the Capricorn District, Limpopo Province, South Africa - Baloyi, Jimmy Patric (My University, 2011)
Since 1994, the post apartheid government and the Department of Health have developed and implemented a number of policies and pieces of legislation that impacted directly and indirectly on the delivery of health services such as the general public health, health personnel, financial matters, transportation of medicines and foodstuffs. These policies were timeously received by the hospitals from National Office, Provincial Departments and Local Government, but were not implemented due to numerous challenges. This study explores the health policy implementation challenges facing implementers in the public health sector in the Capricorn district in Limpopo that constrain them from rendering their managerial functions effectively and thus, impact negatively on policy implementation and service delivery. The objective of the study is to explore the challenges with a view of describing the nature and causes of the challenges, explore and document them, develop suggestions for minimizing these challenges and subsequently suggesting possible solutions. The study focused on the Capricorn district in Limpopo Province. The district is the biggest among the five districts and has eight functional hospitals which are under the leadership of Chief Executive Officers (CEO). The researcher used both qualitative and quantitative (mixed) research methods. The methodology entailed the distribution of self-administered questionnaires containing closed and open ended questions to the management of Capricorn district hospitals. The results obtained in this study revealed that there are numerous challenges that constrain policy implementers from implementing health policies effectively and efficiently in their work environments. These challenges range between poor incentives, lack of equipment, lack of office space, lack of dedicated transport for outreach, budget constraints, shortage of resources – human and physical, lack of career mobility, poor working conditions, communication problems and poor supervision style. These challenges impact negatively on policy implementation.It is therefore recommended that the comprehensive strategy to maximize the health workers’ motivation in the health sector has to involve a mix of financial and non-financial incentives, the provincial department of health and Social Development should open some communication lines with the service providers at grass root level in order to address some of the issues before they become chronic challenges, there should also be regular meetings where feedback about provincial and national issues are addressed to the service providers. The current system of dissemination of information from the province and national government to the hospitals is apparently not clear.
Thesis (MPH) --University of Limpopo, 2011
Keywords: Health policy; 362.10968; Medical policy; Public health -- South Africa; Health planning